Solve :
[tex] \frac{2x}{x – 4 } + \frac{1}{x – 2} + \frac{2}{x {}^{2} – 6x + 8 } = 0[/tex]

Solve :
[tex] \frac{2x}{x – 4 } + \frac{1}{x – 2} + \frac{2}{x {}^{2} – 6x + 8 } = 0[/tex]

1 thought on “Solve : <br />[tex] \frac{2x}{x – 4 } + \frac{1}{x – 2} + \frac{2}{x {}^{2} – 6x + 8 } = 0[/tex]<br />​”

  1. Step-by-step explanation:

    =x−4

    2x

    +

    x−2

    1

    +

    (x−4)(x−2)

    2

    =0

    =2x(x−2)+x−4+2=0

    =2x²−3x−2=0

    =2x²+x−4x−2=0

    =x(2x+1)−2(2x+1)=0

    =(2x+1)(x−2)=0

    =x=− 1/2;2

    this is a answer for this question ⁉️⁉️⁉️⁉️⁉️⁉️⁉️⁉️⁉️⁉️⁉️⁉️❓❓❓

Leave a Comment